Phytochemical characterization and multifaceted bioactivity assessment of essential oil from Clinopodium nepeta subsp. ascendens: potential for the food and pharmaceutical sectors - Mohamed Taibi; Amine Elbouzidi; Mounir Haddou; Yousra Belbachir; Abdellah Baraich; Zineb Khalil; Reda Bellaouchi; Abdeslam Asehraou; Mohamed Addi; Ammar AL-Farga; Saleh M. Al-Maaqar; Bouchra El Guerrouj; et al. (CyTA - Journal of Food)
This study delves into the biological characteristics of Clinopodium nepeta subsp. ascendens (CNEO) essential oil, an indigenous subspecies of eastern Morocco. Distinguished by its purple or pale pinkish-white flowers, CNEO was subjected to thorough phytochemical analysis via gas chromatography-mass spectrometry (GC-MS), revealing 21 terpene compounds, notably Dihydrocarvone (22.70%), Neoisomenthol (43.59%), and Pulegone (20.55%). These compounds, recognized for their biological and pharmacological attributes, were further investigated for their potential applications. Notably, CNEO exhibited dose-dependent anti-inflammatory effects by attenuating nitric oxide (NO) and prostaglandin E2 (PGE2) production. Moreover, it demonstrated promising anticancer activity against MDA-MB-468, HepG2, and HCT-15 cancer cell lines, rivaling doxorubicin’s effectiveness. These findings underscore CNEO’s nutraceutical potential, particularly in food science and industry, suggesting its use as a functional food additive with both nutritional and health benefits